Quorum sensing improves the plant growth-promoting ability of Stenotrophomonas rhizophila under saline-alkaline stress by enhancing its environmental adaptability - Zhuang, Xuliang; Liu, Ying; Fang, Na; Bai, Zhihui; Gao, Jie (Frontiers in Microbiology, 2023)
Quorum sensing (QS) system has an essential function in plant growth-promoting rhizobacteria (PGPR) response to environmental stress and PGPR induction of plant tolerance to saline-alkaline stress. Nevertheless, there is a lack of understanding about how QS influences the growth-promoting effects of PGPR on plants. Stenotrophomonas rhizophila DSM14405T is a PGPR with a QS system, which can secrete diffusible signal factor (DSF), one of the QS signal molecules. In this study, we used the S. rhizophila wild type (WT) and an incompetent DSF production rpfF-knockout mutant strain to explore whether DSF-QS could affect the growth-promoting ability of PGPR in Brassica napus L.. By measuring the seed germination rate, plant fresh weight, biomass, the total antioxidant capacity (T-AOC) level, and the content of chlorophyll in leaves, we found that DSF was unable to enhance the growth-promoting capacity of ΔrpfF and did not directly assist the plants in tolerating saline-alkaline stress. However, DSF aided S. rhizophila ΔrpfF in resisting stress during its effective period, and QS represents a continuous and precise regulatory mechanism. Altogether, our results show that DSF is helpful to improve the environmental adaptability and survival rate of S. rhizophila, thus indirectly improving the germination rate of seeds and helping plants grow under saline-alkaline stress. In this study, the mechanism of QS enhancing the environmental adaptability of PGPR was studied, which provided a theoretical basis for improving the application of PGPR to help plants better cope with saline-alkaline stress.